2018
DOI: 10.3126/ejdi.v23i1-2.19063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Payments for Disease Specific Care on Poverty Estimates in Nepal

Abstract: The popular poverty estimation method follows the cost of basic needs approach through estimation of poverty line. Health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The Nepal NCDI Poverty Commission used data from the 2010–11 Nepal Living Standards Survey to estimate the disease-specific impoverishing effects of NCDIs. 205 , 206 The Nepal Commission found that every case of cancer, high blood pressure, injuries, and heart, kidney, and liver disease could cause between 0·3 and 1·5 cases of poverty. At the population level, injuries, gastrointestinal diseases, and heart disease had the highest effect on impoverishment due to their prevalence.…”
Section: Section 3: Financing To Address Ncdi Povertymentioning
confidence: 99%
“…The Nepal NCDI Poverty Commission used data from the 2010–11 Nepal Living Standards Survey to estimate the disease-specific impoverishing effects of NCDIs. 205 , 206 The Nepal Commission found that every case of cancer, high blood pressure, injuries, and heart, kidney, and liver disease could cause between 0·3 and 1·5 cases of poverty. At the population level, injuries, gastrointestinal diseases, and heart disease had the highest effect on impoverishment due to their prevalence.…”
Section: Section 3: Financing To Address Ncdi Povertymentioning
confidence: 99%